Assessing the Urban Heat Island (UHI) Effect Using Land Surface Temperature (LST) and Normalized Difference Built-Up Index (NDBI): A Case Study on Paphos, Cyprus - Dimitriou, Christodoulos; Michaelides, Silas; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Papadavid, George; Gitas, Ioannis; Kyriakides, Nicholas (My University, 2025)
The Urban Heat Island (UHI) effect is responsible for increased urban temperatures compared to rural areas due to heat-absorbing materials like concrete and asphalt, worsening climate change impacts and creating thermal discomfort for citizens. Limited green spaces reduce natural cooling, increasing health risks. This study examines UHI in Paphos (2015–2024) during significant infrastructure development, using Landsat-9 data to analyze Land Surface Temperature (LST), urban growth (NDBI), and vegetation (NDVI). The results reveal how development has affected the microclimate of Paphos compared with the limitation of green spaces through time series. This study also highlights remote sensing’s effectiveness in assessing UHIs.
Keywords: Urban Heat Island; UHI; Remote sensing; Climate change; Global warming